The double-headed approach of the ECJ concerning consumer protection - Unberath, H; Johnston, AC (Kluwer Law International, 2007)
This article analyses the development of EC consumer law by looking in detail at the approach taken by the European Court of Justice in its case law in this field, and the impact that this had had upon national law in certain areas. It contends that the Court has taken contrasting approaches to the desirable extent of consumer protection laws, depending upon whether that protection derives from national laws which operate as derogations from the EC’s Treaty rules on the internal market or from positive legislative activity at EC level. In the former area, the Court has been unwilling to accept many such national consumer protection measures, regularly finding them not to be necessary for achieving the relevant goal or to be disproportionate to that end. In the latter area, however, the Court has consistently given an expansive interpretation to the provisions in the directives on consumer protection. The reasons behind this difference in approach are discussed and it is suggested that the Court’s support for more interventionist consumer protection measures when interpreting the scope of EC legislation sometimes fails in fact to secure the protection which the Court seems to require, or only does so at the cost of far-reaching effects upon other areas of law and practice in the relevant sectors. In conclusion, it is suggested that these differences relate to the Court’s perception of its function in interpreting and applying the primary rules of the EC Treaty, on the one hand, and in promoting the objectives of secondary law adopted under that Treaty, on the other. Two fundamentally conflicting policies are the result: free trade is the priority of primary legislation while interventionist consumer protection lies at the heart of the case law on secondary legislation. Yet the Court’s holdings merely point to a deeper-level tension in the fabric of the Community’s philosophy of market regulation.